Frequency of Uterine fibroids and related risk factors in women with hysterectomy - Maryam Asghar Neia; Roya‏ Faraji; Seyedeh Noshaz Mir Hagh Jou; Mahsa Karimi (Journal of Holistic Nursing and Midwifery)
Background: Uterine Leiomyoma is the most common benign pelvic tumors. There are different ‎and controversial reports on its frequency and related risk factors.‎